Transgenerational epigenetic inheritance: an open discussion. (August 2015) - Nagy, Corina; Turecki, Gustavo
Much controversy surrounds the idea of transgenerational epigenetics. Recent papers argue that epigenetic marks acquired through experience are passed to offspring, but as in much of the field of epigenetics, there is lack of precision in the definitions and perhaps too much eagerness to translate animal research to humans. Here, we review operational definitions of transgenerational inheritance and the processes of epigenetic programing during early development. Subsequently, based on this background, we critically examine some recent findings of studies investigating transgenerational inheritance. Finally, we discuss possible mechanisms that may explain transgenerational inheritance, including transmission of an epigenetic blueprint, which may predispose offspring to specific epigenetic patterning. Taken together, we conclude that presently, the evidence suggesting that acquired epigenetic marks are passed to the subsequent generation remains limited.